Survey of captive parrot populations around Port Phillip Bay, Victoria, Australia, for psittacine beak and feather disease virus, avian polyomavirus and psittacine adenovirus. Issue 8 (August 2015) - Hulbert, CL; Chamings, A; Hewson, KA; Steer, PA; Gosbell, M; Noormohammadi, AH
<x xml:space="preserve">Abstract</x> Objective This study investigated the prevalence of psittacine beak and feather disease virus (BFDV), avian polyomavirus (APV) and psittacine adenovirus (PsAdV) in captive psittacine birds around Port Phillip Bay, Victoria, Australia. Methods Samples of fresh droppings were collected from 118 psittacine birds (109 clinically normal and 9 with feather abnormalities) from 11 avaries in different locations and were used for detection of BFDV, APV and PsAdV using PCR. Results BFDV, APV and PsAdV were detected in 31%, 13% and 4%, respectively, of the specimens tested. One budgerigar was found to be co‐infected with BFDV and PsAdV. At least one sample tested positive for BFDV at each location. Conclusion This is the first report of the prevalence of BFDV, APV and PsAdV in Victoria and provides a foundation for future studies examining the influence of these viruses on the health of aviary birds in Victoria.